Does a tired mind help solve insight problem? The effect of ego depletion on college professors' insight. (6th March 2020) - Lin, Bo; Li, Huimin; Yu, Jia
Innovation plays an important role in the operation and management of scientific research institutions. According to behavioural science theory, the human plays an important role in the operation and management of an organisation. As the subject of knowledge innovation, the main undertaker of its innovation performance is college professors. In order to explore the influence of different ego depletion on the solution of college professors' insight problem. This paper uses the eye movement experiment to explore the process of solving the insight problems. It is found that there are significant differences between college professors in solving insight problems under different ego depletion. The difference of ego depletion in gender is insignificant, but the difference in age is significant. At the end, some suggestions are put forward to reduce the ego depletion of college professors, improve their innovative performance, and make the college operation and management more effective.